2014
DOI: 10.1002/fam.2284
|View full text |Cite
|
Sign up to set email alerts
|

Improving the performance of fluoroprotein foam in extinguishing gasoline pool fires with addition of bromofluoropropene

Abstract: Summary The fluoroprotein foam is one of the most widely used fire suppressants for its low cost, low toxicity and biodegradability. However, its fire extinguishing performance is limited. In this article, fluoroprotein foam was combined with a clean and degradable fire suppressant of 2‐bromo‐3,3,3‐trifluoropropene (BTP) to improve its fire extinguishing efficiency. Laboratory scale suppression experiments on gasoline pool fires were conducted in a 27 m3 confined space. An optimized volume flow ratio of air to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The use of different types of foaming agents in compressed air foam when extinguishing flammable liquids is studied in [16,[19][20][21]. The authors [8] noted the advantages of the AFFF-type film-forming foaming agent over the synthetic S. The authors [19] claim that when using fluorocarbon surfactants, the foam has an increased film thickness and a lower diffusion coefficient than for protein foaming agents.…”
Section: Literature Analysis and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of different types of foaming agents in compressed air foam when extinguishing flammable liquids is studied in [16,[19][20][21]. The authors [8] noted the advantages of the AFFF-type film-forming foaming agent over the synthetic S. The authors [19] claim that when using fluorocarbon surfactants, the foam has an increased film thickness and a lower diffusion coefficient than for protein foaming agents.…”
Section: Literature Analysis and Problem Statementmentioning
confidence: 99%
“…The authors [8] noted the advantages of the AFFF-type film-forming foaming agent over the synthetic S. The authors [19] claim that when using fluorocarbon surfactants, the foam has an increased film thickness and a lower diffusion coefficient than for protein foaming agents. In [20], the fire-extinguishing efficiency of compressed air foam with fluorine synthetic foaming agent with the content of a chemical compound (2-bromo-3,3,3trifluoropropene) and without it was compared. The extinguishing time is 43 % shorter compared to the fixed foam extinguishing time without adding a chemical compound.…”
Section: Literature Analysis and Problem Statementmentioning
confidence: 99%
“…Zhao et al [14] found that CAF had an excellent extinguishing effect in extinguishing oil tank fires by comparing the low foaming and multiple foam fire-extinguishing systems. Zhao et al [15] studied the combined effect of fluoro-protein foam and BTP in improving the fire suppressing efficiency of foam. Meanwhile, it was found that the foam showed the best efficiency in suppressing oil pool fires at an optimal gas-liquidvolume ratio of 9.…”
Section: Introductionmentioning
confidence: 99%
“…16 Due to the low price and good performance, FP foam has been widely used in recent years to fight the oil fires. 17 However, the fluidity and foam resistance to oil contamination of protein-based foam extinguishing agents are poor, 18 and a high concentration of organic wastewater consisting of various types of natural proteins is produced in the production process, 19 which may cause environmental pollution when discharged. Chemical oxygen demand (COD) is often used as an indicator measuring the organic pollution in water.…”
Section: Introductionmentioning
confidence: 99%